Analisis Faktor-Faktor Kesulitan Siswa dalam Memahami Pembelajaran IPAS (Kurikulum Merdeka) di Sekolah Dasar - Suharyanto; Andi Imrah Dewi; Nurul Fitriah Aras; Azizah Azizah; Muhammad Nazimuddin Al Kamil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the factors contributing to students' difficulties in understanding Natural and Social Sciences (IPAS) learning within the Merdeka Curriculum at SD Al-Khairaat Tondo. The research method used is qualitative descriptive, with data collected through observation, interviews, and documentation. The research subjects consist of third-grade students and IPAS teachers.The findings indicate that students' difficulties are influenced by several factors, including limited understanding of abstract IPAS concepts, low student interest in IPAS subjects, a lack of interactive learning media, and learning strategies that are not yet fully aligned with the characteristics of the Merdeka Curriculum. In conclusion, there is a need to improve contextual learning approaches, utilize more varied media, and provide teacher training in the implementation of the Merdeka Curriculum to enhance students' understanding of IPAS materials. Keywords: IPAS, Learning Difficulties, Merdeka Curriculum, Contextual Learning, Elementary School Students.